Evaluation of Cytotoxicity and Mutagenicity of Wastewater from Istanbul: Data from Hospitals and Advanced Wastewater Treatment Plant - SÜSLEYİCİ, BELGİN; DARTAN, GÜLER; CİNEL, İSMAİL HAKKI; AKSU, MEHMET BURAK; LAÇİN, TUNÇ; YURDUN, TÜRKAN; KESKİN, YAŞAR; CAN, ZEHRA SEMRA (SPRINGER, 2020)
Wastewater (WW) carry considerable amount of chemicals that could have mutagenic or cytotoxic effect from hospital discharges to aquatic environment. Our objective was to determinate the possible mutagenic and toxic effects of hospital originated WWs and effectiveness of the wastewater treatment plants (WTP) functions. In the study the mutagenic and cytotoxic potential of three hospitals and influent/effluent of a treatment plant WW collected in Istanbul and was examined using AMES, XTT, and lactate dehydrogenase (LDH) assays. Mutagenic effects were detected at both hospital discharges and advanced biological wastewater plant. We observed no cytotoxic effect in fibroblasts for LDH and XTT assays whereas high cytotoxicity for all samples was found in hepatocytes by XTT assay. According to the results even if advanced technology is used for treatment of WW, mutagenic and cytotoxic effects still remain, and the present technologies need to be further improved.
Keywords: Wastewater; Hospital wastewater; Wastewater treatment plant; Mutagenicity; Cytotoxicity; SURFACE-WATER; GENOTOXICITY; RIVER; TOXICITY; QUALITY; CANCERS; METALS